SHM_109204_HST_3D Vendel I Helmet - Lernestål, Erik; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of the Vendel I helmet, an iron helmet with applied bronze decorations including remains of figure scenes of pressed sheet metal. The helmet was excavated from an Iron Age boat grave (Vendel I) in Vendel Parish, Uppsala County and is currently held in the collections of the National Historical Museums in Stockholm.

Link to Sök I Samlingarna

https://samlingar.shm.se/object/F0DD41E6-54C5-41FC-9AE4-C865CD8FEB2F

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=847
Keywords: Photogrammetry; Archaeology; Archaeology; Archaeology/history; History and archaeology; 3D Model; Museum Object; Dynamic Collections; Vendel; Swedish Iron Age; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi